2004
DOI: 10.1097/01.ju.0000108136.41620.95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microwave Thermotherapy With Histopathology, Magnetic Resonance Imaging and Temperature Mapping

Abstract: Coretherm microwave treatment causes significant tissue necrosis of the prostate, bladder neck and urethral mucosa. The cell kill calculation provides an on-line estimate of the amount of necrosis caused during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…6,7 Such approaches have been used to characterize a number of thermal therapies for the treatment of BPH-LUTS. [8][9][10][11][12] Lesion visualization helps the clinician understand the effects of treatment on the surrounding tissues, dosage adequacy, and lesion location in relation to the placement of the needle and the ablative region.…”
mentioning
confidence: 99%
“…6,7 Such approaches have been used to characterize a number of thermal therapies for the treatment of BPH-LUTS. [8][9][10][11][12] Lesion visualization helps the clinician understand the effects of treatment on the surrounding tissues, dosage adequacy, and lesion location in relation to the placement of the needle and the ablative region.…”
mentioning
confidence: 99%
“…Prostate lesions caused by thermotherapy were detected in all patients 1 week after the treatment by using contrast medium-enhanced, T1-weighted MR images and showed a significant correlation with the lesion size calculated by the device. Huidobro et al [4], using the same device, reported nearly comparable results for their 12 patients investigated 4Á16 days after thermotherapy with gadolinium-enhanced MRI. In their study, the correlation between calculated cell kill and lesion size assessed by MRI was 0.8 (pB 0.0001).…”
Section: Discussionmentioning
confidence: 65%
“…Although previous studies comparing cell-kill calculations with prostate shrinkage measured by either two-dimensional or three-dimensional transrectal ultrasonography found that cell-kill calculations with the PLFT method assess the volume of necrosis reasonably well 16,21 and yield results consistent with observations regarding actual prostate-volume reduction after TUMT, 15,21 a recent study that combined cell-kill calculations with MRI and histopathologic findings showed that there is an intra-individual standard deviation of Ϯ 10 cc when combining all three methods of assessing coagulation necrosis. 22 We were unable to correlate the actual cell-kill number with the patient's outcome. This result is in agreement with the results of other authors showing that the reduction in prostate volume is similar in nonresponders and responders.…”
Section: Discussionmentioning
confidence: 99%